Sport fans using social media: A study on celebrity sports fans (Sport and Tourism Central European Journal, 2023)
Social media has become an essential platform for sports fans, athletes, clubs, and teams. This study provides a comprehensive review of the last decade’s research developments in social media, with a particular focus on how sports fans utilize this technology to engage with their interests. The study’s objectives are to explore how sports fans use social media to connect with their favorite athletes and teams, identify relevant theories and concepts that explain the significance of social media for sports fans, and analyze sports fans’ behavior and interactions on social media. Based on a review of 29 selected articles, the study finds that social media serves as a means for fans to express their fandom and that their identities and interactions on social media are framed by use and gratification theory, which is commonly employed in fan and social media research. Additionally, the study reveals that sports feminism has emerged among fans. While instances of racist comments and behavior among diehard fans remain a downside, it is crucial to investigate the importance of digital literacy among sports fans.